The Influence of Perceptions of the Public Accountant Profession, Adversity Intelligence, Financial Awards and Labor Market Considerations on the Interests of Accounting Students for a Career to Become a Public Accountant (Study of Accounting Students at : Pengaruh Persepsi Profesi Akuntan Publik, Kecerdasan Adversity, Penghargaan Finansial dan Pertimbangan Pasar Kerja Terhadap Minat Mahasiswa Akuntansi Untuk Berkarir Menjadi Akuntan Publik (Studi Pada Mahasiswa Akuntansi Universitas Muhammadiya - Azizah, Nur; Hariyanto, Wiwit (Journal of Islamic and Muhammadiyah Studies, 2022)
This study aims to determine the effect of perceptions of the public accounting profession, adversity intelligence, financial rewards, and labor market considerations on the interest of accounting students to have a career as public accountants. This study uses a quantitative approach to analysis techniques. The objects used in this study were accounting students from the 2017 and 2018 batches at the Muhammadiyah University of Sidoarjo. The sample used is 78 respondents using purposive sampling method, by distributing questionnaires through google form. The data analysis used is multiple regression analysis using SPSS version 26 application. The results of this study show that only financial rewards do not affect the interest of accounting students to have a career as public accountants. Meanwhile, the perception of the public accounting profession, adversity intelligence, and labor market considerations affect the interest of accounting students to have a career as public accountants.